Tangokuninkaalliset 2018 - Kokko, Jarno; Sassali, Saana; Almila, Atso; Toivanen, Mika; Seinäjoen Orkesteri (GRF-Records / Sony Music Finland Oy, 2018)
12 kappaletta.
Keywords: 2010-luku; tangot (sävellykset); Suomi